EXTH-83. TARGETING DNA REPAIR AND SURVIVAL PATHWAYS THROUGH HEAT SHOCK PROTEIN INHIBITION USING AT13387 TO SENSITIZE GLIOMA TO CHEMORADIATION THERAPY. (6th November 2017) - Wu, Jasmine P J; Canella, Alessandro; Xu, Jihong; Lai, Tzung-Huei; Welker, Alessandra M; Beattie, Christine E; Nadella, Vijay; Timmers, Cynthia; Kaur, Balveen; Jacob, Naduparambil; Sampath, Deepa; Puduvalli, Vinay K
Abstract: BACKGROUND: Glioblastoma (GBM) is the most lethal of adult primary brain tumors. Resistance to the standard chemoradiation therapy with temozolomide (TMZ) emerges due to increased expression of DNA-alkylating proteins and potent DNA repair. This is in part through activation of the heat-shock response, an evolutionally conserved defense mechanism mediated by heat-shock proteins (HSP). We recently reported that AT13387, an orally-bioavailable second generation HSP90 inhibitor, efficiently crosses the blood brain barrier (BBB) and is effective preclinically against gliomas as a single agent and in combination with TMZ. METHODS AND RESULTS: To test whether its potent effects on DNA-repair pathways could sensitize GBM to chemoRT, we examined the effects of AT13387 in glioma cell lines and patient-derived glioma stem-like cells. AT13387 potently induced apoptosis, inhibited key oncogenic pathways and inhibited proliferation and migration of glioma cells. RPPA and RNAseq analysis revealed reduced expression of several key DNA-repair proteins and genes. AT13387-treated glioma cells exposed to radiation showed impaired ability to repair DNA in NHEJ/HR DNA-repair assays and increased DNA damage in a Comet assay. The combination of AT13387 with TMZ and RT showed in vivo efficacy with significant improvement in survival in intracranial GBM-xenotransplanted zebrafish and in an intracranial glioma PDX nude mouse model compared with radiotherapy alone or chemoRT. Lastly, AT13387-treated ex vivo human glioma slice cultures showed reduced levels of DNA repair and survival pathway proteins and increased g-H2AX levels indicating DNA damage compared with untreated controls. CONCLUSIONS: The oral bioavailability, ability to cross the BBB and multi-target pathway inhibition by AT13387 makes it a promising agent for therapeutic targeting of GBM. Our results also strongly support the potential for Hsp90 inhibition with AT13387 as a therapeutic strategy against gliomas in combination with chemoradiation therapy. A phase I/II trial of the combination in newly-diagnosed GBM patients is currently under planning.